2018
DOI: 10.18632/oncotarget.23892
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Midkine expression in patients with solid tumors: a systematic review and meta-analysis

Abstract: BackgroundAccumulated studies have shown the important role of Midkine (MDK) protein in various solid tumors and indicated its correlation with patients’ survival. This meta-analysis was performed to further explore the prognostic value of MDK expression in solid tumors.Materials and MethodsWe collected the literatures through searching PubMed, Embase and the Cochrane Library (last up to April 10, 2017) to assess the effect of MDK on survival in solid tumor patients. The STATA 12.0 software was used for the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…MDK expression is induced by cytokines and growth factors, mainly by TNF-α [55], and it acts through activating the NFkβ and MAPK/PI3K proliferative pathway [54]. In clinical studies, MDK was considered a potential prognostic biomarker in solid tumors [56]. In breast cancer patients, it was suggested as both a diagnostic and a prognostic biomarker [57,58].…”
Section: Effect Of the Investigated Ceramides On The Tumor Weightmentioning
confidence: 99%
“…MDK expression is induced by cytokines and growth factors, mainly by TNF-α [55], and it acts through activating the NFkβ and MAPK/PI3K proliferative pathway [54]. In clinical studies, MDK was considered a potential prognostic biomarker in solid tumors [56]. In breast cancer patients, it was suggested as both a diagnostic and a prognostic biomarker [57,58].…”
Section: Effect Of the Investigated Ceramides On The Tumor Weightmentioning
confidence: 99%
“…Meta-regression and subgroup analyses were performed to further explore the potential source of heterogeneity. Funnel plot, Egger's test, and Begg's test were performed to evaluate the publication bias [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Elevated MK serum levels are found in patients with different tumor entities and have been shown to correlate with poor prognosis and recurrence after tumor removal [ 2 , 3 , 4 ]. The tumor cells may be the source of MK in this case, as malignant tissue often shows high MK expression [ 5 ]. The low plasma levels of MK in healthy subjects are rapidly elevated upon administration of heparin.…”
Section: Midkinementioning
confidence: 99%
“…We have previously shown that angiogenesis is severely impaired in MK-deficient mice, suggesting that MK also regulates the bioavailability of leukocyte-derived VEGF-A for endothelial cell proliferation in capillary sprouting [ 37 ]. These findings might have a major impact on the treatment of highly vascularized tumors as well, as tumor cells are likely to produce MK [ 5 ] to promote or even induce the vascularization of the tumor tissue itself. Accordingly, MK may represent a powerful tumor target.…”
Section: Arteriogenesismentioning
confidence: 99%
See 1 more Smart Citation